Dynamic Contrast-enhanced MRI in Renal Tumors: Common Subtype Differentiation using Pharmacokinetics - Hai-yi Wang (Nature Portfolio, 2017)
Abstract Preoperative renal tumor subtype differentiation is important for radiology and urology in clinical practice. Pharmacokinetic data (K trans & V e, etc.) derived from dynamic contrast-enhanced MRI (DCE-MRI) have been used to investigate tumor vessel permeability. In this prospective study on DCE-MRI pharmacokinetic studies, we enrolled patients with five common renal tumor subtypes: clear cell renal cell carcinoma (ccRCC; n = 65), papillary renal cell carcinoma (pRCC; n = 12), chromophobic renal cell carcinoma (cRCC; n = 9), uroepithelial carcinoma (UEC; n = 14), and fat-poor angiomyolipoma (fpAML; n = 10). The results show that K trans of ccRCC, pRCC, cRCC, UEC and fpAML (0.459 ± 0.190 min−1, 0.206 ± 0.127 min−1, 0.311 ± 0.111 min−1, 0.235 ± 0.116 min−1, 0.511 ± 0.159 min−1, respectively) were different, but V e was not. K trans could distinguish ccRCC from non-ccRCC (pRCC & cRCC) with a sensitivity of 76.9% and a specificity of 71.4%, respectively, as well as to differentiate fpAML from non-ccRCC with a sensitivity of 100% and a specificity of 76.2%, respectively. Our findings suggest that DCE-MRI pharmacokinetics are promising for differential diagnosis of renal tumors, especially for RCC subtype characterization and differentiation between fpAML and non-ccRCC, which may facilitate the treatment of renal tumors.